2016
DOI: 10.1016/j.cmi.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiologic study of Clostridium difficile reveals unusual heterogeneity in clinical strains circulating in different regions in Portugal

Abstract: Clostridium difficile infection (CDI) represents a great healthcare burden in developed countries. The emergence of the epidemic PCR ribotype (RT) 027 and its acquired fluoroquinolones resistance have accentuated the need for an active surveillance of CDI. Here we report the first countrywide study of CDI in Portugal with the characterization of 498 C. difficile clinical isolates from 20 hospitals in four regions in Portugal regarding RT, virulence factors and antimicrobial susceptibility. We identified 96 RTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Strains of other ribotypes, including RT078 and RT017, which have enhanced virulence, have emerged ( 6 ). In particular, RT017, the most common toxin A–negative, toxin B–positive ribotype, is widespread in Asia and is common in Europe ( 7 9 ). In a pan-European study of ≈900 C. difficile strains, the overall rate of resistance to imipenem, an antimicrobial drug of the carbapenem class, currently widely used as a last-line drug to treat infections by gram-negative bacteria, was found to be 7.41%, and the geometric mean (GM) MIC of imipenem for RT017 strains was 5.91 mg/L ( 8 ).…”
mentioning
confidence: 99%
“…Strains of other ribotypes, including RT078 and RT017, which have enhanced virulence, have emerged ( 6 ). In particular, RT017, the most common toxin A–negative, toxin B–positive ribotype, is widespread in Asia and is common in Europe ( 7 9 ). In a pan-European study of ≈900 C. difficile strains, the overall rate of resistance to imipenem, an antimicrobial drug of the carbapenem class, currently widely used as a last-line drug to treat infections by gram-negative bacteria, was found to be 7.41%, and the geometric mean (GM) MIC of imipenem for RT017 strains was 5.91 mg/L ( 8 ).…”
mentioning
confidence: 99%
“…The rates of resistance vary considerably between countries; however, this is likely due to differences in ribotype diversity, since the countries with higher diversity of ribotypes tend to exhibit lower rates of fluoroquinolones resistance and vice versa [146]. This same trend was observed in Portugal when comparing ribotype diversity and resistance rates between regions [194]. Fluoroquinolone resistance in C. difficile, as a result of antibiotics use selective pressure, is associated with well-known mutations in the quinolone-resistance determining region of DNA gyrase subunits gyrA and gyrB.…”
Section: Fluoroquinolonesmentioning
confidence: 62%
“…In Portugal, CDI surveillance based on a network of sentinel hospitals has been carried out since 2010, and showed that RT017 is one the most common ribotypes circulating in the country [194]. In particular, one RT017 clone was shown to be endemic in a hospital from 2012 until today, and a different RT017 clone has emerged in another hospital in the beginning of 2016 (our unpublished data).…”
Section: Antibiotic Resistance and The Emergence And Spreading Of Epimentioning
confidence: 86%
See 2 more Smart Citations